Solve for x 3-4x=5x-6 Subtract 5x from both sides to get 3-4x-5x=-6 Subtract 3 from both sides to get -4x-5x=-6-3 Combine like terms on each side to get -9x=-9 Divide each side by -1 to get 9x=9 Divide each side by 9 to get x=1 Answer x=1
5x + 3 = 4xSubtract 3 from each side:5x = 4x - 3Subtract 4x from each side:x = -3
20x^2 + 27x + 9 = 0 20x^2 + 15x +12x + 9 = 0 5x(4x + 3) + 3(4x + 3) = 0 (5x + 3)(4x + 3) = 0 So either (5x + 3) = 0 which yields x = -3/5 or (4x + 3) = 0 which yields x = -3/4
9x = 60x = 60/9 = 6 2/3 (or 6.67)
5x + 14 = 95 - 4x 5x + 4x = 95 - 14 9x = 81 x = 81/9 x = 9
5x - 9 = 4x 5x - 4x - 9 = 4x - 4x x - 9 = 0 x - 9 + 9 = 0 + 9 x = 9
5x = 4x + 9 x = 9
If your equation is 5x-2=4x+4 Then this is how you solve it... 5x-2=4x+4 5x-2+2=4x+4+2 5x=4x+6 5x-4x=4x-4x+6 x=6 Your x=6
Solve for x 3-4x=5x-6 Subtract 5x from both sides to get 3-4x-5x=-6 Subtract 3 from both sides to get -4x-5x=-6-3 Combine like terms on each side to get -9x=-9 Divide each side by -1 to get 9x=9 Divide each side by 9 to get x=1 Answer x=1
5x + 3 = 4xSubtract 3 from each side:5x = 4x - 3Subtract 4x from each side:x = -3
-5x + x + 9 = -4x + 12 -4x + 9 = -4x + 12 9 = 12 This equation has no solution.
4x - 3 - 5x + 7 = 6 4x - 5x = 3 - 7 + 6 -1x = 2 x = -2
20x^2 + 27x + 9 = 0 20x^2 + 15x +12x + 9 = 0 5x(4x + 3) + 3(4x + 3) = 0 (5x + 3)(4x + 3) = 0 So either (5x + 3) = 0 which yields x = -3/5 or (4x + 3) = 0 which yields x = -3/4
9x = 60x = 60/9 = 6 2/3 (or 6.67)
5x + 14 = 95 - 4x 5x + 4x = 95 - 14 9x = 81 x = 81/9 x = 9
4x - 10 + 5x = 719x = 81x = 9
1x-5x = -4x But since you had the absolute value symbols surrounding it, change it to positive; so the answer is: 4x